A Cascade Aza‐Cope/Aza‐Prins Cyclization Leading to Piperidine Derivatives. Issue 9 (5th February 2015) - Nallasivam, Jothi L.; Fernandes, Rodney A.
Abstract: The cascade aza‐Cope/aza‐Prins cyclization of homoallylamines to give substituted piperidines has been explored. The use of glyoxalic acid as the carbonyl component afforded bicyclic structures as a result of the internal carboxylate anion trapping the intermediate cation. The unimolecular bis‐, tris‐, and tetrakis(homoallylamine)s efficiently delivered the appended bis‐, tris‐ and tetrakis(piperidine‐4‐ol)s (tripod and crucifix shape, respectively) as new entities. The latter compound served as an excellent ligand in the Suzuki–Miyaura cross‐coupling reaction to synthesize incrustoporin. Abstract : The cascade aza‐Cope/aza‐Prins cyclization of homoallylamines to give substituted piperidines is described. A unimolecular tetrapiperidine derivative, which resulted from this strategy, was employed as a ligand in the Suzuki–Miyaura cross‐coupling reaction of an α‐iodobutenolide with an arylboronic acid in an efficient synthesis of incrustoporin and its analogues.